(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2023)
Relational Frame Theory (RFT) is a theoretical proposal to explain empirical evidence related to the behavioral phenomenon of derived relational responding, with theoretical and applied implications, especially regarding human verbal behavior. Although RFT is having a significant and progressively larger impact on behavioral science, most of its publications are in English, which impairs its accessibility to the Brazilian behavior analytic community. Thus, this paper’s main objective is to introduce RFT’s fundamental concepts to readers familiar with behavior analytic basic principles. This will include the philosophical foundation of Functional Contextualism; the behavioral phenomena of (non-arbitrary, arbitrary and derived) relational responding; the concepts of Arbitrarily Applicable Relational Responding (AARR) and relational frames, including their properties and learning history; and, lastly, the dimensions of AARR.